Answer:
We conclude that:
Explanation:
Given
We know that the diagonals of a parallelogram bisect each other.
so
![RT = TP](https://img.qammunity.org/2022/formulas/mathematics/high-school/bfwhtu0ng1crvld0oguuwhji188n7j1wsv.png)
Given
so substituting RT = x, and TP = 5x-28
![RT = TP](https://img.qammunity.org/2022/formulas/mathematics/high-school/bfwhtu0ng1crvld0oguuwhji188n7j1wsv.png)
![x = 5x-28](https://img.qammunity.org/2022/formulas/mathematics/high-school/absm8h0w85muikavuw0g8dwcida48r06l4.png)
![5x = x+28](https://img.qammunity.org/2022/formulas/mathematics/high-school/iic0d4cnz02mgmqsthp0cbb663fd5obxuo.png)
![5x-x = 28](https://img.qammunity.org/2022/formulas/mathematics/high-school/w228thq2626190yzcscnw9p62wo1mcdsyk.png)
![4x = 28](https://img.qammunity.org/2022/formulas/mathematics/high-school/hwl31vhm1fsuisg0tlihxc6d0tiudco8lp.png)
divide both sides by 4
![4x/4 = 28/4](https://img.qammunity.org/2022/formulas/mathematics/high-school/3atrnxsmvjno8igkf660070ztoqz5mfqt3.png)
![x = 7](https://img.qammunity.org/2022/formulas/mathematics/college/bf53fqeffext1l0o2vdrwy0k70p8jnc19d.png)
Therefore, the value of x:
Similarly,
![QT = TS](https://img.qammunity.org/2022/formulas/mathematics/high-school/kxe441sdvqf7ltgl9a50f3it1l22e8etg2.png)
Given
so substituting QT = 5y, and TS = 2y+12
![QT = TS](https://img.qammunity.org/2022/formulas/mathematics/high-school/kxe441sdvqf7ltgl9a50f3it1l22e8etg2.png)
![5y = 2y+12](https://img.qammunity.org/2022/formulas/mathematics/high-school/4kx1f9p5dmnt9kln4jg7ku8o4oof3ogrj7.png)
![5y-2y = 12](https://img.qammunity.org/2022/formulas/mathematics/high-school/ng102zprr8ldwiomhs7jnkk812e9n5ub3n.png)
![3y = 12](https://img.qammunity.org/2022/formulas/mathematics/high-school/x365911187x9mubeui14ludxxb3cyvjt7o.png)
divide both sides by 3
![3y/3 = 12/3](https://img.qammunity.org/2022/formulas/mathematics/high-school/nz1vllvybcg5bfekbtjsoe2igsi01240il.png)
![y = 4](https://img.qammunity.org/2022/formulas/mathematics/high-school/94j3g602mbwktbb8ux2t7t8euy50372sna.png)
Therefore, the value of y:
y = 4
Therefore, we conclude that: